ANALYSIS OF FINANCIAL RATIO ON INFLUENCING THE GROWTH OF RESIDUAL OPERATING RESULTS IN SAVINGS AND LOAN COOPERATIVES (KSP) - Pranoto, Sarastanto Aulia Heru; Sarbullah, Sarbullah; Prahmawati, Kristi Ary (JURNAL STIE SEMARANG, 2024)
Abstract. This study aims to analyze and explain the influence of CR (Current Ratio), DAR (Debt to Asset Ratio), TATO ( Total Asset Turnover) and NPM (Net Profit Margin) ratios on the growth of Remaining Business Results (RBR) at the Mitra Sejahtera Blora Sayings and Loans Cooperative (SLC) in 2016-2022. This research aims to test the effect CR, DAR, NPM, and ne profit margins on RBR at the cooperative since 2016. The results show that the current ratio has a significant effect on the overall growth of the remaining business results at the cooperative. The DAR ratio has an important effect on the overall growth of RBR. The current ratio, net profit margin, and total assets turnover have an important influence on growth. The NPM ratio has no significant influence on the total assetss turnover. The net profit margin in significant effect is obcerved in the remaining operating results. This means that the number of liabilities under one year or equal to one year is compared to total current assets. Increasing the remaining business results of a cooperative is very dependent on the activities it carries out. In 2022 the current ratio at the Mitra Sejahtera Blora Savings and Loans Cooperative (KSP) will increase to 0.96%. In 2019 and 2020 the current ratio increased to 0.99%, and fell again in 2021 to 0.90%. The greater the remaining business results obtained indicate better financial performance, because the rate of return is greater. And in 2022 the dept to asset ratio at the Mitra Sejahtera Blora Savings and Loans Cooperative (SLC) will increase to 0.71%.